Melawan Arus Modernitas: Tantangan Masyarakat Banten Lama dalam Mempertahankan Tradisi Panjang Mulud - SALMAN; Dinar Sugiana Fitrayadi; Aryanti Dwi Untari (STKIP Subang, 2025)
Local wisdom is an important part of a society's cultural identity and plays a major role in shaping the collective consciousness of citizens. However, in the midst of the rapid flow of globalization, the existence of local values ​​is experiencing significant pressure. The younger generation is now increasingly exposed to foreign cultures that are considered more interesting and modern, causing a disconnection from the history and traditions of their own region. In the Old Banten area, the long tradition of Mulud as one form of local wisdom is starting to face serious challenges in its preservation. The lack of knowledge of the younger generation about Banten culture and history shows symptoms of fading traditional values. This condition strengthens the urgency of strengthening civic culture, namely a culture of citizenship that reflects awareness, attitudes, and active participation in the social life of society. Civic culture grows from a sense of belonging to the community and its cultural heritage, and therefore strengthening local wisdom is a strategic step to build cultural resilience and strengthen national character. Through understanding and active involvement of the community in preserving culture, local wisdom can remain alive and relevant in today's social dynamics.